Asphyxiation effect analysis in confined space of B-type oil pool fire under pressure changes of nitrogen extinguishing system - Feiyue Wang; Weixuan Li; Litian Wan; Long Yan; Zhisheng Xu (Case Studies in Thermal Engineering)
Nitrogen fire extinguishing system has a significant development space in the modern fire extinguishing because of its environmental protection, energy saving and high stability. To further broaden the application field of nitrogen fire extinguishing system, a shrinkage size model was used as the research object and combined with simulated flow field analysis. A nitrogen fire extinguishing system was characterized for alcohol fire extinguishing efficacy using nitrogen injection pressure as a variable and parameters such as extinguishing time, oxygen concentration, and temperature. Furthermore, diesel and gasoline were used as combustible materials to verify the extinguishing efficacy of pressure variation on Class B oil pool fires. It was found that with the increase of nitrogen injection pressure, the nitrogen extinguishing efficacy gradually increased and then leveled off in the confined space. The asphyxiating oxygen concentrations were 12.2 %, 13.2 % and 13.7 % for ethanol, diesel and gasoline, respectively. Asphyxiating oxygen concentration above limiting oxygen concentration (LOC). For extinguishing Class B oil pool fires in confined spaces, nitrogen extinguishing systems showed excellent fire extinguishing efficiency. They had specific application prospects in the field of protecting underground oil storage tanks and oil wells.